Pengembangan Soal Pemecahan Masalah Bentuk Formatif untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP Negeri 1 Glenmore - Fasihah, Uswatun; Fatqurhohman, Fatqurhohman; Rhomdani, Rohmad Wahid (Supermat : Jurnal Pendidikan Matematika, 2024)
This study research to enhance students' critical thinking skills through formative tests in the form of mathematical problem-solving. This study employs a 3D development model, including define, design, and develop stages. The research was conducted by preparing formative test questions, having them validated by subject matter experts, and then testing them on the VIII A grade students of SMP Negeri 1 Glenmore. The testing was carried out in two stages: small group and large group. The small group consisted of 10 students, while the large group comprised 32 students. The research findings show that the validation stage received 88.33% from validator 1, and 81.67% from validator 2. Both scores from the validators met the criteria of being highly suitable for testing. During the trials, the teacher's response scored 90% with a category of strongly agree, and the students' response scored 90% as well with the same category. In the small group trial, the students' response score was 80.75%, and in the large group, it was 81.48%, both achieving the strongly agree criterion. Therefore, the developed product is highly appropriate for use.